Targeting Sedentary Behavior in CKD: A Pilot and Feasibility Randomized Controlled Trial. Issue 5 (8th May 2021) - Lyden, Kate; Boucher, Robert; Wei, Guo; Zhou, Na; Christensen, Jesse; Chertow, Glenn M.; Greene, Tom; Beddhu, Srinivasan
Visual Abstract: Abstract : Background and objectives: We tested the feasibility of reducing sedentary behavior common in CKD. Design, setting, participants, & measurements: We carried out a Sit Less, Interact, Move More intervention in a 24-week parallel-group, randomized controlled trial in patients with stages 2–5 CKD. In the intervention group ( n =54), accelerometry performed at baseline and repeated every 4 weeks was used to develop and monitor adherence to individualized plans targeting sedentary and stepping durations. The control group ( n =52) was provided national physical activity recommendations; accelerometry was performed at baseline and every 8 weeks. Between-groups changes from baseline to the average follow-up values at weeks 8, 16, and 24 of the sedentary and stepping durations were the coprimary end points. Results: The mean age was 69±13 years. Fourteen percent were on dialysis or received a kidney transplant. Eight percent of the control group and 17% of the intervention group were lost to follow-up. Sedentary and stepping durations did not change in the control group. Within the intervention group, the maximum decrease in sedentary duration (−43; 95% confidence interval, −69 to −17 min/d) and increase in stepping duration (16; 95% confidence interval, 7 to 24 min/d) and the number of steps per day (1265; 95% confidence interval, 518 to 2012) were seen at week 20. These attenuated at week 24. In mixed effects models, overall treatment effects between groups on sedentary (−17; 95% confidence interval, −43 to 8 min/d) and stepping (6; 95% confidence interval, −3 to 15 min/d) durations and the number of steps per day, a secondary end point (652; 95% confidence interval, −146 to 1449), were not significantly different. The intervention significantly reduced secondary end points of body mass index (−1.1; 95% confidence interval, −1.9 to −0.3 kg/m 2 ) and body fat percentage (−2.1%; 95% confidence interval, −4.4% to −0.2%). Conclusions: It is feasible to reduce sedentary duration and increase stepping duration in patients with CKD, but these were not sustained. Clinical Trial registry name and registration number: National Health and Nutrition Examination Survey (NHANES), NCT02970123